Dysfunction, activity limitations, participation restriction and contextual factors in South African women with pelvic organ prolapse - Corlia Brandt; Elizabeth C. Janse van Vuuren (AOSIS, 2019)
Background: Pelvic organ prolapse (POP) is a multifactorial, poorly understood condition impacting quality of life (QOL). The pathology and aetiology might imply population-specific differences in domains of the International Classification of Function, Disability and Health (ICF). There is, however, a lack of research in this regard in South Africa. Objectives: To describe the dysfunction, activity limitations, participation restrictions and contextual factors in South African women with POP. Method: One hundred women were conveniently sampled in a primary health care setting. They completed a self-compiled medical and exercise history questionnaire, the standardised Prolapse-Quality of Life (P-QOL) questionnaire and the Visual Faces Scale. The stage of prolapse was determined by the Pelvic Organ Prolapse Quantification (POP-Q) Scale. Means, medians, standard deviations, percentages and frequencies were calculated. Results: Eighty-six per cent had a stage III POP, 57% had overactive bladder, 50% had constipation, 37% had stress urinary incontinence, 31% had urge urinary incontinence, 32% had incomplete emptying and 30% had anal incontinence. Comorbidities included cardiovascular disease (65%), depressive symptoms (12%) and hypothyroidism (18%). Other contextual factors included limited physical activity (80%), an increased body mass index (29 kg/m2), older age (59 years) and unemployment (80%). Quality of life was affected in the severity, social, emotional and sleep/energy domains (median scores were 66.7% - 33.3%). Conclusion: The dysfunction domain of the ICF was similar to other populations with POP. Activity and participation restrictions included social, emotional and sleep/energy aspects. Contextual factors seem to be population-specific, possibly leading to differences comparing QOL amongst different populations. Clinical implications: Activity and participation restrictions, as well as contextual factors, may differ in different populations with POP. Interactions between contextual factors and movement impairment should be considered during management and be further investigated.